Ms. Marvel meets the Marvel Universe - Wilson, G. Willow, 1982- (Marvel Worldwide, Inc., 2020)
Kamala Kahn is an average Pakistani teenager except she is secretly Ms. Marvel. After an encounter with Wolverine, Spider-Man, and even her idol, Captain Marvel, Kamala realizes her true calling as a superhero. She tries to balance school and normal teenage problems as she learns to master her powers and handle the weight of being an Inhuman.